The Role Of Alternative Media In Building Social Awareness: A Study Of Independent Podcasts In Indonesia - Syawaludin, Dwi Febri (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2025)
In the context of media fragmentation and declining public trust in mainstream journalism, independent podcasts in Indonesia have emerged as alternative spaces for public discourse. These digital platforms enable marginalized voices and critical narratives to reach wider audiences, offering an avenue for civic engagement and grassroots activism. This study aims to explore how independent podcasts contribute to the formation of social awareness, identify the communication strategies used by podcasters, and map patterns of listener interaction as a form of participatory citizenship. Employing a qualitative approach, the research integrates digital ethnography, semi-structured interviews, and critical discourse analysis. Data were collected from 15 independent podcast channels, 12 in-depth interviews with podcasters and active listeners, and content analysis of 30 podcast episodes discussing social, political, and environmental themes. The findings reveal that independent podcasters act as organic intellectuals who use personal storytelling, emotional resonance, and ideological framing to raise social consciousness. The most common themes include human rights, labor issues, gender equality, and environmental justice. Audience engagement extends beyond listening—listeners share content, participate in discussions, donate, and even mobilize offline action. The study recommends supporting independent podcast production through funding, training in critical media literacy, and expanding accessibility to underserved communities. Independent podcasts represent not only an emerging media form but also a democratic communication model capable of reshaping public dialogue in Indonesia.